Fondasi Ekonomi Berkeadilan dalam Masyarakat Multikultural - Dewi, Arlinta Prasetian (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study aims to examine the practice of interfaith business ethics and local wisdom as the foundation for realizing a just economy in the Buddhist Village of Ponorogo, known as a community with religious diversity, tolerance, and strong local wisdom. The study uses a qualitative approach with a case study method, through interviews, observations, and document and literature reviews. The results show that local wisdom in the form of mutual cooperation, water resource management, social forest utilization, and cultural ritual practices have become the basis for strengthening the community economy and a space for actualizing interfaith business ethics values ​​​​reflected in cooperation between Buddhists and Muslims in daily economic activities, based on the values ​​​​of honesty, mutual respect, and sharing benefits. The integration of local wisdom and interfaith business ethics gives rise to a just economic pattern that ensures equal access to resources, strengthens social cohesion, and encourages sustainable development. This study concludes that the Buddhist Village represents a model of a multicultural society that has succeeded in building a just economic foundation through religious harmony and local wisdom.